ANALISIS STRATEGI PEMASARAN PT. TARUNAGRAHA PERSADA PERUMAHAN PANORAMA BANJARAN SEMARANG - Gustina Gustina; Urai Sulia Sukmawati (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
The purpose of this study was to determine the marketing strategy at PT. Tarunagraha Persada, especially the Panorama Banjaran Semarang housing complex, is based on a SWOT analysis. The research problem is that the more competitive and selective consumers are in choosing the products available in the market, the company must find the right strategy in paying attention to the company's internal and external environment. Collecting data in this study using interviews and observations, interviewing marketing staff and obtaining data on the real situation in the Panorama Banjaran Semarang housing area. The results showed that the SO strategy (strengths and opportunities), namely by maintaining the quality of the products produced in order to increase sales in conditions of higher market growth, ST strategy (strengths and threats) by increasing the quality of the products produced in the face of competition from old competitors who are growing in a good direction and in facing new competitors that produce more innovative products. Then, the WO strategy (weaknesses and opportunities), namely by understanding what consumers want and increasing understanding why consumers deserve to buy the products we offer given the excellent market potential and higher market growth. Aniway, the WT strategy (weaknesses and threats) is to improve business strategies in a better direction by making different strategies from competitors.